Efficient Resource Allocation in a Multinucleated City - John M. Hartwick; Philip G. Hartwick (Queen's University, Department of Economics, 1972)
Mills' programming model of efficient resource allocation in an urban area is extended to include multiple nuclei and intermediate goods. The new model is a decomposable linear program in which the primary resource value of the city plus transportation costs are minimized subject to a prescribed bill of final demands for the city and to land constraints consisting of cells in a areal grid. Shadow prices on land emerge in the dual problem.
Keywords: 330